2011
DOI: 10.1111/j.1467-8624.2011.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subjective Recollection: Understanding of and Introspection on Memory States

Abstract: The development of subjective recollection was investigated in participants aged 6-18 years. In Experiment 1 (N = 90), age-related improvements were found in understanding of the subjective experience of recollection, although robust levels of understanding were observed even in the youngest group. In Experiment 2 (N = 100), age-related differences were found in subjective recollection during a memory task, suggesting development not only in the ability to reflect on memory states, but also in the informationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 47 publications
5
65
0
1
Order By: Relevance
“…These various components of metamemory may follow different developmental trajectories (e.g., Fritz, Howie, & Kleitman, 2010) and may partially account for the development of memory functions. Indeed, the presence of metamemory functions in children younger than 8 years is debatable (DeMarie & Ferron, 2003; but see also Ghetti, Mirandola, Angelini, Cornoldi, & Ciaramelli, 2011;Larkin, 2007;Pressley & Hilden, 2006). It is plausible that the protracted development of metamemory observed in this study may mirror the developmental trajectories of memory and its neural correlates (Ofen, 2012;Ofen et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…These various components of metamemory may follow different developmental trajectories (e.g., Fritz, Howie, & Kleitman, 2010) and may partially account for the development of memory functions. Indeed, the presence of metamemory functions in children younger than 8 years is debatable (DeMarie & Ferron, 2003; but see also Ghetti, Mirandola, Angelini, Cornoldi, & Ciaramelli, 2011;Larkin, 2007;Pressley & Hilden, 2006). It is plausible that the protracted development of metamemory observed in this study may mirror the developmental trajectories of memory and its neural correlates (Ofen, 2012;Ofen et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Although previously believed to reach adult levels by middle childhood, newer studies illustrate that episodic memory develops considerably through adolescence, such that the full integration of the capabilities of the PFC and the anterior and posterior networks of the MTL does not occur until young adulthood (Ghetti and Angelini, 2008; Ghetti and Bunge, 2012; Brainerd et al, 2004; Ghetti and Bauer, 2011; Ghetti et al, 2011). This integration has been credited to the maturation of cognitive control processes, including those involved in context maintenance and response inhibition (Jaeger et al, 2012; O’Connor et al, 2010), semantic organization of items (Schwenck et al, 2009), and the ability to monitor memory accuracy (Ghetti and Alexander, 2004; Ghetti and Castelli, 2006; Ghetti et al, 2008; DeMarie and Ferron, 2003), that occurs during the teen years.…”
Section: Discussionmentioning
confidence: 99%
“…A first study by Perner and Ruffman (1995) suggested that young children could not reliably differentiate remembering and knowing; children could not judge what originates from personal experience before the age of 3. In a more recent study, Ghetti et al (2011) also asked children to classify memories into “Remember” or “Familiar” categories. They showed that 6- to 7-year-olds found it difficult to differentiate between states of recollection and familiarity but their level of understanding was nonetheless above chance.…”
Section: Typically Developing Childrenmentioning
confidence: 99%
“…Ghetti et al (2011) explored whether or not the nature of the subjective recollection changed during childhood, and whether the qualitative details of memories changed. In their Experiment 2, children were shown line drawings presented either in red or green.…”
Section: Typically Developing Childrenmentioning
confidence: 99%